MEDIA PROMOSI KESEHATAN FILM PENDEK MENGENAI PENCEGAHAN ANEMIA BAGI SISWA KELAS XI (Jurnal Kesehatan Siliwangi, 2021)
Anemia or lack of red blood cells is still quite high and the program for giving TTD to teenagers during 2020 at the Pasir Mulya Health Center is still not optimal, the use of short film media is one of the media that teenagers are interested in because the media is young to understand. The purpose of this study was to produce a short film health promotion media about anemia prevention for teenagers. The research used a mixed methods research with The exploratory sequential design research design which began with in-depth interviews with users to explore needs and create prototypes, then conducted a feasibility test on 1 media expert, 1 material expert, and 61 students of Rimba Madya High School Bogor City. The results of the study obtained media expert assessment of 96% in the category of "very valid", material expert assessment of 97% in the category of "very valid", and assessment of media usability for users of 4.47 in the category of "excellent", as well as assessment of user knowledge with wilcoxon p value test results p value > 0,05= 0,001 so the data concluded that the media developed after going through the exploration and prototyping phase obtained the result that the media and materials are very feasible to use and the usefulness of the media for users is very good, as well as the significant influence of short film media interventions on the improvement of knowledge about anemia prevention of grade XI students of Rimba Madya High School. The recommendation of this study is that developed media should make positive changes in adolescents, especially towards anemia prevention behavior.